Methodology for Semi-Automatic Development of Cloud-based Business Applications - Benfenatki, Hind; Ferreira da Silva, C.; Benharkat, Aïcha-Nabila; Ghodous, P.; Biennier, F. (Proc. of 7th IEEE International Conference on Cloud Computing, 2014)
The purpose of this paper is to define a generic methodology for semi-automatic development of cloud-based business applications. This can be used by non-IT experts, such as business stakeholders, who trigger a business application development by simply stating its requirements in terms of business functionalities and constraints, QoS parameters, and her/his preferences. From these functionalities and constraints, Linked USDL requirements files are automatically generated. These files provide the basis for the cloud service discovery and launch the automatic development of cloud business applications. We present the first developments of our prototype.